Small bowel metastasis with multiple sites of perforation caused by anaplastic thyroid carcinoma metastasis: A case report - Taengsakul, Nawaphan (Journal of the Association of General Surgeons of Thailand under the Royal of Patronage of HM the King, 2024)
Introduction: Anaplastic thyroid carcinoma (ATC) is an extremely aggressive cancer with a very poor prognosis. The lungs, pleura, adrenal glands, and liver are the most common sites of metastasis; metastasis to the digestive tract is rare. Case presentation: The patient was a 63-year-old man with ATC was treated with pembrolizumab and lenvatinib. Concomitant venous thromboembolism was being treated with direct oral anticoagulants. He developed peritonitis, and revealed perforation sites associated with an intestinal mass. Clinical discussion: ATC with small bowel metastasis is uncommon. However, physicians should be aware of this possibility, especially in patients planned targeted therapy. Conclusion: Small bowel metastasis of ATC is rare and results in tumor-associated perforation. Small bowel metastasis should be investigated in patients with ATC who present with gastrointestinal hemorrhage. Evidence of small bowel metastasis influences the choice of anticoagulant and systemic cancer treatment in ATC patients.